1999
DOI: 10.1023/a:1020106409700
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria Present in Excised Patches From Pancreatic B-cells May Form Microcompartments With ATP-Dependent Potassium Channels

Abstract: Experiments with inside-out patches excised from pancreatic B-cells have yielded evidence that mitochondria are often contained in the cytoplasmic plug protruding into the tip of patch pipette. When intact B-cells were loaded with the fluorescent mitochondrial stain, rhodamine 123, and membrane patches excised from these cells, a green fluorescence could be observed in the lumen at the tip of the patch pipette. The same result was obtained with the mitochondrial stain, MitoTracker Green FM, which is only fluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…As described in other systems (Kennedy et al 1999; Montero et al 2000), peripheral mitochondria may form functional units with membrane proteins to delimit submembraneous cytosolic microdomains. These ideas are compatible with previous observations describing the modulation of membrane K + channels by O 2 tension in excised membrane patches (Ganfornina & López‐Barneo, 1991; Riesco‐Fagundo et al 2001; Lewis et al 2002) as these are known to contain mitochondria and other intracellular organelles (Sather et al 1992; Rustenbeck et al 1999). The existence of a separate sensor that confers O 2 sensitivity to the K + channels helps to explain why in some conditions, in which the sensor is possibly detached from the channels, glomus cells lose the responsiveness to hypoxia while maintaining normal electrophysiological properties (López‐Barneo et al 1998).…”
Section: Discussionsupporting
confidence: 92%
“…As described in other systems (Kennedy et al 1999; Montero et al 2000), peripheral mitochondria may form functional units with membrane proteins to delimit submembraneous cytosolic microdomains. These ideas are compatible with previous observations describing the modulation of membrane K + channels by O 2 tension in excised membrane patches (Ganfornina & López‐Barneo, 1991; Riesco‐Fagundo et al 2001; Lewis et al 2002) as these are known to contain mitochondria and other intracellular organelles (Sather et al 1992; Rustenbeck et al 1999). The existence of a separate sensor that confers O 2 sensitivity to the K + channels helps to explain why in some conditions, in which the sensor is possibly detached from the channels, glomus cells lose the responsiveness to hypoxia while maintaining normal electrophysiological properties (López‐Barneo et al 1998).…”
Section: Discussionsupporting
confidence: 92%
“…They concluded that the O 2 -sensing function was not intrinsic to the Kv2.1-Kv9.4 complex, on the basis of the fact that only some transfected cells responded to low O 2 concentration (45). However, an alternative interpretation is based on a recent report by Rustenbeck et al (52), who found that mitochondria were present in excised membrane patches from pancreatic ␤-cells. The possibility that mitochondria may remain associated with ATP-sensitive K ϩ (K ATP ) channels by being dragged into the pipette during inside-out excised patch experiments raises the possibility that such organelles could be involved in the O 2 -sensing response.…”
Section: The O 2 -Sensitive Ion Channel Hypothesismentioning
confidence: 99%
“…Thus, plasma membrane-compartmentalized PK must be sufficiently close to the K ATP channel to locally deplete MgADP and increase ATP to close the channel. An alternative interpretation of this data is that PK-derived pyruvate is oxidized by residual patch-associated mitochondria that generate ATP and close K ATP channels independently of glycolysis 33 . However, pyruvate and ADP were unable to induce K ATP channel closure, and the presence of ATP synthase inhibitor (1 μg/mL oligomycin) did not affect K ATP channel inhibition by PEP and ADP (Supplemental Figure S1).…”
Section: Resultsmentioning
confidence: 98%
“…In mammalian cells, glycolysis is known to regulate a variety of plasma membrane ion channels and pumps that exist in regions of high ATP consumption, including K 18 . Cardiac K ATP channels are known to associate with multiple enzymes of lower glycolysis which regulate the channel via the activity of PK 2528 . However, the demonstration of a complete glycolytic metabolon—involving the communication of substrates and nucleotides between upper and lower glycolysis as well as LDH—remains elusive.…”
Section: Introductionmentioning
confidence: 99%